The Diversity of Medicine Plant in Repong Damar Agroforestry of Krui, Lampung Province - Susanti, Amelia Dwi; Wijayanto, Nurheni; Hikmat, Agus (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
Utilization of medicinal plants by Krui People those whose raw materials come from agroforestry “Repong Damar” has long been known and this knowledge has been passed down from generation to generation. Repong Damar is a term for agroforestry in Krui. Research has been conducted in Mei-Juni 2018 with the aim to known the species of plant as utilizing medicinal plants. Data were collected through direct interview with snowball sampling technique and field observations. The results showed that 93 species of plants from 40 families were used as medicine. The highest family is Piperaceae (10%). The most widely used plant parts are 46% of leaves and the type of disease that is often treated as medicinal plants is respiratory tract. Keywords: agroforestry, repong damar, medicinal plants